A kind of pervious concrete material based on shield waste soil and preparation method

CN120794487BActive Publication Date: 2026-11-03CCCC TUNNEL ENG CO LTD +3
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510985860.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-07-17
Publication Date
2026-11-03
Estimated Expiration
2045-07-17

AI Technical Summary

Technical Problem

Existing technologies make it difficult to effectively utilize waste soil from tunnel boring machines to precisely control the pore structure in permeable concrete, resulting in unstable permeability and mechanical properties, which limits its application in urban infrastructure.

Method used

By employing a synergistic design of surface-modified shield tunnel waste soil coarse aggregate and biodegradable pore-forming agent particles, and by modifying the aggregate surface with γ-aminopropyltriethoxysilane, combined with a corn starch-based pore-forming agent with a double-layer cross-linked structure, staged pore-forming and strength coordination are achieved, forming a stable pore structure.

Benefits of technology

It has enabled the high-value utilization of waste soil from tunnel boring machines, improved the permeability and structural stability of permeable concrete, solved the problem of balancing early strength and permeability, and optimized the uniformity and connectivity of the pore structure.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120794487B_ABST
    Figure CN120794487B_ABST
Patent Text Reader

Abstract

The application relates to the field of concrete. In view of the problems of low utilization rate of shield waste soil resources and difficulty in accurate control of the pore structure of pervious concrete in the prior art, surface modified shield waste soil coarse aggregate and degradable pore-forming agent particles are used as core components, the bonding performance of the aggregate is improved through surface modification of gamma-aminopropyl triethoxysilane, a corn starch-based double-layer cross-linked structure pore-forming agent is designed to realize staged degradation, the early-stage degradation rate constant is 0.04-0.08 d ‑1 , the late-stage degradation rate constant is 0.12-0.18 d ‑1 , and the material is prepared by combining cementitious materials, water and other components to prepare pervious concrete. The material significantly improves the utilization rate of waste soil resources, the bonding strength of the aggregate and the cement paste is increased by 30-60%, the stability degradation rate of the pore-forming agent is less than 5% in the first 48 hours after the concrete is poured, the shell degradation rate reaches 25-35% in the third to seventh days, the total degradation rate reaches 70-85% in the seventh to twenty-eighth days, an accurately controllable connected pore network is formed, and the material is suitable for sponge city construction, road paving and other engineering applications.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of concrete materials, specifically to a permeable concrete material based on tunnel boring machine waste soil and its preparation method. Background Technology

[0002] With the rapid development of urban underground space, shield tunneling is widely used in large-scale infrastructure construction such as subways, tunnels, and integrated utility tunnels. The resulting large amounts of waste soil not only occupy land resources but also pose a potential environmental pollution risk. Simultaneously, the demand for permeable concrete materials in urban stormwater management systems has increased significantly. This type of material plays a crucial role in urban roads, plazas, sidewalks, and sponge city infrastructure, requiring excellent permeability, mechanical strength, and durability, while maintaining the stability and connectivity of its pore structure over long periods in complex environments. Therefore, constructing a permeable concrete system that combines structural load-bearing capacity with moisture regulation has become a core requirement for promoting green urban infrastructure construction. In this context, achieving high-value utilization of shield tunneling waste soil and precisely controlling the pore structure of concrete can not only improve the material's functional performance and service life but also significantly reduce engineering costs and environmental burden, promoting the integrated development of shield tunneling construction and eco-friendly building materials. Therefore, developing a permeable concrete material based on shield tunneling waste soil not only aligns with the green and low-carbon development direction of urban construction but also has significant implications for improving the solid waste recycling system and enhancing the performance of urban infrastructure.

[0003] Although some studies have attempted to utilize tunnel boring machine (TBM) waste soil in building materials, and others have focused on optimizing the pore structure of permeable concrete, significant shortcomings remain in efficiently utilizing TBM waste soil in permeable concrete and achieving precise control over its pore structure. For example, Chinese patent CN109293318B discloses a permeable concrete that proposes utilizing slag, but fails to effectively address the controllability issue of the permeable concrete's pore structure, leading to unstable permeability and mechanical properties in practical applications. The fundamental reason lies in the complex composition, high moisture content, and uneven particle distribution of TBM waste soil. Direct application easily causes fluctuations in aggregate properties, while traditional pore-forming methods rely heavily on physical foaming or single degradation mechanisms, making it difficult to achieve systematic control over the pore structure's formation time, connectivity, and spatial distribution. Therefore, existing material systems generally lack in-depth design for the functional coupling of aggregate modification and pore-forming agents, resulting in a difficulty in balancing structural density and permeability in the resulting concrete. This limits the application space of TBM waste soil in high-performance permeable concrete and restricts its potential for promotion in sustainable urban construction. Summary of the Invention

[0004] (1) Technical problems to be solved

[0005] The purpose of this invention is to provide a permeable concrete material and preparation method based on shield tunneling waste soil, and to solve the technical problems of resource utilization of shield tunneling waste soil and precise control of the pore structure of permeable concrete.

[0006] (2) Technical solution

[0007] To achieve the above objectives, the present invention provides the following technical solution:

[0008] A permeable concrete material based on shield tunneling waste soil comprises the following components in parts by weight: 85-95 parts of surface-modified shield tunneling waste soil coarse aggregate, 5.0-15 parts of biodegradable pore-forming agent particles, 15-35 parts of cementitious material, 10-25 parts of water, 0.5-1.5 parts of admixture, and 1.0-3.0 parts of fine aggregate;

[0009] The surface-modified shield tunnel waste soil coarse aggregate is obtained by surface modification of shield tunnel waste soil coarse aggregate with γ-aminopropyltriethoxysilane;

[0010] The mineral composition of the coarse aggregate of the shield tunnel waste soil is as follows: quartz content 15.0-35.0 wt%, feldspar content 10.0-25.0 wt%, and total clay mineral content 40.0-60.0 wt%, of which montmorillonite content does not exceed 20.0 wt% of the total clay mineral content;

[0011] The biodegradable pore-forming agent particles are spherical particles with a double-layer cross-linked structure designed with corn starch as the base material. The core is modified with highly cross-linked glutaraldehyde to provide structural stability, while the outer shell is modified with low-cross-linked glutaraldehyde to achieve staged degradation. They are prepared by rotary granulation.

[0012] Furthermore, the mass ratio of the coarse aggregate of the tunnel boring machine waste soil to the biodegradable pore-forming agent particles is (85-95):(5-15).

[0013] This invention employs a synergistic design of surface-modified coarse aggregate from tunnel boring machine (TBM) waste soil and biodegradable pore-forming agent particles, primarily to enhance the structural stability and pore control performance of permeable concrete. The technical solution utilizes γ-aminopropyltriethoxysilane to surface-modify the coarse aggregate from TBM waste soil, significantly improving the interfacial compatibility between the waste soil aggregate and cementitious materials, thus solving the bonding performance defects caused by insufficient surface activity of traditional waste soil materials. The formation of the surface-modified layer constructs an organosilicon-modified network structure on the aggregate surface, enhancing the chemical bonding between the aggregate and cement paste, providing a reliable mechanical support foundation for permeable concrete. The biodegradable pore-forming agent particles adopt a double-layer cross-linked structure design based on corn starch. The highly cross-linked glutaraldehyde modification of the core ensures the structural integrity of the particles during concrete pouring and early hardening, avoiding the uneven pore distribution problem caused by the easy breakage of traditional pore-forming materials. The low-cross-linked glutaraldehyde modification of the outer shell achieves a staged and controllable degradation mechanism, ensuring that the pore-forming process is coordinated with the development of concrete strength. The synergistic mechanism between surface-modified aggregates and bilayer pore-forming agents lies in the enhanced interfacial bonding properties provided by the modified aggregates, which create a favorable matrix environment for the stable existence of pore-forming agent particles. Meanwhile, the phased degradation process of the pore-forming agent fully utilizes the structural support provided by the modified aggregates, resulting in an organic unity of mechanical properties and permeability. The rational ratio of aluminosilicate minerals such as quartz and feldspar to clay minerals in the coarse aggregates of shield tunnel waste soil provides abundant reactive sites for surface modification. Simultaneously, the controlled montmorillonite content avoids the adverse effects of excessive expansion on material stability, ensuring the durability and reliability of the modification effect.

[0014] Furthermore, the biodegradable pore-forming agent particles adopt a double-layer cross-linked structure design, with a core cross-linking degree of 15.0-20.0% and an outer shell cross-linking degree of 6.0-10.0%. The average core size is 2.0-6.0 mm, and the total size after outer shell coating is 2.5-8.0 mm. It maintains structural stability within the first 48 hours after concrete pouring, with a degradation rate of <5%. The outer shell begins to degrade from day 3 to day 7, with a degradation rate of 25-35%. From day 7 to day 28, the core is fully degraded, with a total degradation rate of 70-85%. Its degradation kinetics are divided into two stages: in the early stage (0-7 days), the rate constant k1 is 0.04-0.08 d⁻¹, and in the later stage (7-28 days), the rate constant k2 is 0.12-0.18 d⁻¹.

[0015] Furthermore, the preparation method of the coarse aggregate of the shield tunneling waste soil includes the following steps performed sequentially: First, the waste soil is dehydrated and passed through a 5mm square-hole sieve to obtain a silty clay substrate with a moisture content of 15-25%; then, a compound curing agent prepared by mixing 42.5 grade ordinary Portland cement, Grade II quicklime and F type fly ash at a mass ratio of 1:(0.8-1.2):(0.9-1.1) is added, and the mixing water is adjusted to achieve a liquidity index of 0.2-0.6; next, the mixture is stirred in a twin-shaft forced mixer at a speed of 350-450 rpm for 20-40 minutes, and then 5-20mm ellipsoidal particles are prepared by a roller granulator with an pressure of 8-12MPa; then, the mixture is cured at 20-30℃ and relative humidity of 85-95% for 7-28 days, using a mist curing system instead of directly spraying carbonate buffer solution; finally, after sieve grading, the coarse aggregate of the shield tunneling waste soil is obtained.

[0016] Furthermore, the average size of the coarse aggregate from the tunnel boring machine waste soil is 8.0–20.0 mm.

[0017] Furthermore, the method for preparing the bilayer structure of the pore-forming agent particles includes the following steps: First, corn starch is dried to a moisture content ≤3%, mixed with water at a mass ratio of 1:(2.5~3.5), and gelatinized by stirring at 75~85℃ for 30~40 minutes; after the gelatinized liquid is cooled to 50~60℃, 0.3~0.5% of glutaraldehyde by weight of the dry starch is added to carry out the core cross-linking reaction, controlling the pH value at 6.5~7.0, and reacting at a constant temperature for 100~120 minutes; after the reaction is completed, 0.4~0% of dry starch by weight of the dry starch is added. The reaction was terminated with 0.5% sodium sulfite; then the reaction product was granulated into core particles by passing it through a rotary granulator with a sieve aperture of 4-9 mm and a rotation speed of 25-45 rpm; the core particles were dried to a moisture content of ≤3% and then immersed in a starch gelatinization solution containing 0.1-0.2% glutaraldehyde for outer shell coating, with a coating thickness of 0.2-0.5 mm, and reacted at 50-60℃ for 30-45 minutes; finally, they were dried at 55-65℃ for 2-3 hours until the moisture content was ≤5%, and the pore-forming agent particles with a double-layer cross-linked structure were collected.

[0018] Furthermore, the cementitious material is composed of 42.5 grade ordinary Portland cement and F type fly ash in a mass ratio of 1:(0.15-0.45), and the hydration products contain 15.0-25.0 wt% calcium hydroxide, 8.0-15.0 wt% ettringite, 40.0-55.0 wt% hydrated calcium silicate gel, and the balance being unreacted cement.

[0019] Furthermore, the admixture includes a retarder, which is selected from sodium citrate.

[0020] Furthermore, the preparation method of the surface-modified shield tunnel waste soil coarse aggregate includes the following steps: First, the cured aggregate is rinsed with deionized water to remove loose particles and soluble salts from the surface, and then dried at 40-50°C for 1-2 hours; then, a 2-5% by mass γ-aminopropyltriethoxysilane ethanol solution is prepared, and the pH is adjusted to 4.0-5.0 to promote silane hydrolysis; next, the aggregate is immersed in the solution, with a liquid-to-solid ratio of 3:1-5:1, and treated at 40-60°C for 2-4 hours; after treatment, it is dried at 50-60°C for 2 hours to allow silane molecules to condense on the aggregate surface to form a stable organosilicon modified layer. After this treatment, the bonding strength between the aggregate and cement paste can be increased by 30-60% compared with the untreated aggregate.

[0021] Furthermore, the fine aggregate is natural sand with a fineness modulus of 2.3 to 3.0.

[0022] This invention employs a synergistic design of a double-layer cross-linked pore-forming agent particle and a compound curing agent to treat coarse aggregate from tunnel boring machine (TBM) waste soil. This preparation primarily enhances the porosity control performance and structural stability of permeable concrete. The technical solution utilizes a double-layer structure design of glutaraldehyde-crosslinked modified corn starch-based pore-forming agent particles to achieve precise temporal control of the pore-forming process. The highly cross-linked core structure provides stable structural support in the early stages of concrete pouring, ensuring uninterrupted early strength development. The low-cross-linked outer shell structure begins to degrade after the concrete has largely hardened, forming an initial pore network. Subsequently, the complete degradation of the core completes the construction of the final interconnected pores. This staged degradation mechanism avoids the structural defects caused by the simultaneous degradation of traditional pore-forming materials. The coarse aggregate from the TBM waste soil is treated with 42.5 grade ordinary Portland cement, Grade II quicklime, and a compound curing agent of F-type fly ash, achieving the gelatinization transformation of the waste soil. Cement provides the main gel strength, quicklime promotes the stabilization reaction of clay minerals, and F-type fly ash enhances the pozzolanic activity. The synergistic effect of these three components forms an artificial aggregate with excellent mechanical properties. Surface modification treatment utilizes the hydrolysis-condensation reaction of γ-aminopropyltriethoxysilane under acidic conditions to form an organosilicon-modified layer on the aggregate surface, significantly improving the interfacial bonding performance between the aggregate and the cementitious material. The blending of 42.5 grade ordinary Portland cement and Class F fly ash in the cementitious material fully leverages their complementary advantages. The rapid hydration of cement provides early strength, while the later pozzolanic reaction of fly ash continuously improves the interfacial structure. The multiphase coexistence structure of calcium hydroxide, ettringite, and hydrated calcium silicate gel in the hydration products provides a suitable chemical environment for the stable existence and orderly degradation of the pore-forming agent particles. The addition of sodium citrate retarder slows down the hydration rate of the cementitious material, providing ample time for the positioning of the pore-forming agent particles and the full compaction of the concrete, ensuring a uniform distribution of the pore structure. The rational gradation of natural sand fine aggregate fills the voids between coarse aggregates, forming a layered pore structure system with the double-layered pore-forming agent particles, achieving an optimized balance between permeability and mechanical properties.

[0023] This invention also discloses a method for preparing permeable concrete material based on tunnel boring machine waste soil, comprising the following steps:

[0024] S1. Premix the surface-modified shield tunnel waste soil coarse aggregate and biodegradable pore-forming agent particles in a dry state for 3-6 minutes;

[0025] S2. Add the cementitious material and dry mix for 5-10 minutes to form a continuous coating layer on the surface of the aggregate;

[0026] S3. Dissolve the additive in water to form a solution, and slowly add it to the above mixture at a rate of 50-100 mL / min. Stir at a speed of 250-350 rpm for 10-18 minutes until the slump of the mixture reaches 80-120 mm.

[0027] S4. Cast the mixture into a mold, and compact it using a vibrating table with a vibration frequency of 50-80Hz for 45-90 seconds. During the mixing process, maintain the system temperature at 25-35℃ using a circulating water bath.

[0028] S5. Under standard curing conditions of 20±2℃ and relative humidity ≥95%, the concrete is cured to the designed age. The pore-forming agent particles remain stable for the first 48 hours to provide early strength development for the concrete. From the 3rd to the 7th day, the outer shell gradually degrades to form initial pores. From the 7th to the 28th day, the inner core fully degrades to form the final interconnected pore network.

[0029] This invention employs a preparation method that synergistically designs surface-modified shield tunneling waste soil coarse aggregate with biodegradable pore-forming agent particles, primarily used to enhance the permeability and strength of permeable concrete materials. The design objectives of this technical solution are mainly reflected in three core aspects: resource utilization, pore structure optimization, and performance coordination. From a resource utilization perspective, shield tunneling waste soil, as a large amount of waste generated during urban underground engineering construction, can be used as coarse aggregate after surface modification treatment. This solves the waste soil disposal problem and provides an economically feasible raw material source for permeable concrete, achieving high-value utilization of waste. Surface modification treatment can improve the surface characteristics of shield tunneling waste soil and enhance its interfacial bonding performance with cementitious materials, laying the foundation for subsequent strength development. From the perspective of pore structure design, the introduction of biodegradable pore-forming agent particles is a key technical means to achieve permeability. Its unique staged degradation mechanism makes the pore formation process sequential and controllable. The first 48 hours of stabilization provide necessary support for the early strength development of concrete, avoiding the early strength loss problems that may occur with traditional pore-forming methods. From day 3 to 7, the gradual degradation of the outer shell forms initial pores, creating conditions for the initial establishment of permeability. From day 7 to 28, the full degradation of the inner core forms the final interconnected pore network, ensuring that the permeable concrete possesses excellent permeability. Precise control of the preparation process parameters reflects the synergistic effect between the multi-component materials. Premixing in a dry state ensures the uniform distribution of surface-modified shield tunnel waste soil coarse aggregate and biodegradable pore-forming agent particles. The addition of cementitious materials and the dry mixing process form a continuous coating layer on the aggregate surface, enhancing the interfacial bonding strength. The slow addition of the admixture solution and controlled stirring speed ensure the uniformity and workability of the mixture. Vibration compaction ensures the density of the concrete, while precise control of temperature and humidity provides the most suitable environmental conditions for the synergistic effect of each component. This multi-component synergistic design organically unifies the strength contribution of the surface-modified shield tunnel waste soil coarse aggregate with the permeability of the biodegradable pore-forming agent particles. This ensures both the structural integrity of the permeable concrete and excellent permeability. At the same time, the phased pore formation mechanism avoids the contradiction between early strength and permeability, achieving coordinated optimization of performance. Ultimately, it forms a high-performance permeable concrete material that combines good strength and permeability.

[0030] (3) Beneficial technical effects

[0031] 1. This invention achieves the dual goals of high-value utilization of waste materials and improved performance of permeable concrete through the synergistic effect of surface-modified coarse aggregate from shield tunnel waste soil and biodegradable pore-forming agent particles, effectively solving the technical problem that traditional permeable concrete is difficult to balance in terms of early strength and permeability.

[0032] 2. This invention achieves phased pore formation and coordinated strength development through the synergistic design of double-layer cross-linked pore-forming agent particles and compound curing agent for treating waste soil, thus solving the technical bottleneck of traditional permeable concrete where early strength loss and pore uniformity are difficult to balance. Attached Figure Description

[0033] Figure 1 This is a microstructure morphology image of the permeable concrete prepared in Example 1 of the present invention, 20 days after its pouring.

[0034] Figure 2 The image shows the XRD phase analysis of the coarse aggregate from the tunnel boring machine waste soil prepared in Example 1 of this invention.

[0035] Figure 3 This is a comparison chart of compressive strength and number of freeze-thaw cycles for embodiments and comparative examples of the present invention.

[0036] Figure 4 This is a comparison chart showing the relationship between permeability coefficient and effective porosity in the embodiments and comparative examples of the present invention.

[0037] Figure 5 This is a comprehensive comparison chart of wear loss rate and freeze-thaw resistance performance of the embodiments and comparative examples of the present invention.

[0038] Figure 6 The above is a radar chart showing the combined performance of the embodiments and comparative examples of the present invention.

[0039] Figure 7 This is a series of performance optimization trend charts for embodiments of the present invention. Detailed Implementation

[0040] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings.

[0041] Example 1

[0042] A permeable concrete material based on shield tunneling waste soil comprises the following components in parts by weight: 90 parts of surface-modified shield tunneling waste soil coarse aggregate, 8.0 parts of biodegradable pore-forming agent particles, 25 parts of cementitious material, 18 parts of water, 1.0 part of admixture and 2.0 parts of fine aggregate;

[0043] The surface-modified shield tunnel waste soil coarse aggregate is obtained by surface modification of shield tunnel waste soil coarse aggregate with γ-aminopropyltriethoxysilane;

[0044] The mineral composition of the coarse aggregate of the tunnel boring machine waste soil is as follows: quartz content 25.0 wt%, feldspar content 17.5 wt%, and total clay mineral content 50.0 wt%, of which montmorillonite content does not exceed 15.0 wt% of the total clay mineral content;

[0045] The biodegradable pore-forming agent particles are spherical particles with a double-layer cross-linked structure designed with corn starch as the base material. The core is modified with highly cross-linked glutaraldehyde to provide structural stability, while the outer shell is modified with low-cross-linked glutaraldehyde to achieve staged degradation. They are prepared by rotary granulation.

[0046] In this embodiment, the mass ratio of coarse aggregate from tunnel waste soil to biodegradable pore-forming agent particles is 90:8.

[0047] Furthermore, the biodegradable pore-forming agent particles adopt a double-layer cross-linked structure design, with a core cross-linking degree of 17.5% and an outer shell cross-linking degree of 8.0%. The average core size is 4.0 mm, and the total size after outer shell coating is 5.2 mm. It maintains structural stability within the first 48 hours after concrete pouring, with a degradation rate of <5%. The outer shell begins to degrade from day 3 to day 7, with a degradation rate of 30%. From day 7 to day 28, the core is fully degraded, with a total degradation rate of 80%. Its degradation kinetics are divided into two stages: the rate constant k1 is 0.06 d⁻¹ in the early stage (0-7 days) and the rate constant k2 is 0.15 d⁻¹ in the later stage (7-28 days).

[0048] The method for preparing coarse aggregate from tunnel boring machine waste soil in this embodiment includes the following steps performed sequentially: First, the waste soil is dehydrated and passed through a 5mm square-hole sieve to obtain a silty clay substrate with a moisture content of 20%; then, a compound curing agent prepared by mixing 42.5 grade ordinary Portland cement, grade II quicklime, and type F fly ash in a mass ratio of 1:1.0:1.0 is added, and the mixing water is adjusted to achieve a liquidity index of 0.4; next, the mixture is stirred at 400 rpm for 30 minutes in a twin-shaft forced mixer, and then 12mm ellipsoidal particles are prepared by a 10MPa roller granulator; subsequently, the mixture is cured for 14 days at 25℃ and 90% relative humidity, using a mist curing system instead of directly spraying carbonate buffer solution; finally, after sieve grading, the coarse aggregate from the tunnel boring machine waste soil is obtained.

[0049] The average size of the coarse aggregate from the shield tunneling waste soil in this embodiment is 14.0 mm.

[0050] The method for preparing the bilayer structure of the pore-forming agent particles in this embodiment includes the following steps: First, corn starch is dried to a moisture content ≤3%, mixed with water at a mass ratio of 1:3.0, and gelatinized by stirring at 80°C for 35 minutes; after the gelatinized liquid is cooled to 55°C, 0.4% glutaraldehyde by weight of the dry starch is added to carry out the core cross-linking reaction, the pH value is controlled at 6.8, and the reaction is carried out at a constant temperature for 110 minutes; after the reaction is completed, 0.45% sodium sulfite by weight of the dry starch is added to terminate the reaction; then the reaction product is shaped into core particles by passing it through a rotary granulator with a sieve aperture of 6.5 mm and a rotation speed of 35 rpm; after the core particles are dried to a moisture content ≤3%, they are immersed in a starch gelatinized liquid containing 0.15% glutaraldehyde to coat the outer shell with a coating thickness of 0.35 mm, and reacted at 55°C for 37 minutes; finally, they are dried at 60°C for 2.5 hours until the moisture content is ≤5%, and the pore-forming agent particles with the bilayer cross-linking structure are collected.

[0051] The cementitious material in this embodiment is composed of 42.5 grade ordinary Portland cement and F type fly ash in a mass ratio of 1:0.3. The hydration products contain 20.0 wt% calcium hydroxide, 11.5 wt% ettringite, 47.5 wt% hydrated calcium silicate gel, and the balance unreacted cement.

[0052] The admixture in this embodiment includes a retarder, which is selected from sodium citrate.

[0053] The preparation method of surface-modified shield tunnel waste soil coarse aggregate in this embodiment includes the following steps: First, the cured aggregate is rinsed with deionized water to remove loose particles and soluble salts from the surface, and then dried at 45°C for 1.5 hours; then, a 3.5% (w / w) γ-aminopropyltriethoxysilane ethanol solution is prepared, and the pH is adjusted to 4.5 to promote silane hydrolysis; next, the aggregate is immersed in the solution with a liquid-to-solid ratio of 4:1, and treated at 50°C for 3 hours; after treatment, it is dried at 55°C for 1.5 hours to allow silane molecules to condense on the aggregate surface to form a stable organosilicon modified layer. After this treatment, the bond strength between the aggregate and cement paste can be increased by 45% compared with the untreated aggregate.

[0054] In this embodiment, the fine aggregate is natural sand with a fineness modulus of 2.65.

[0055] This embodiment describes a method for preparing permeable concrete material based on waste soil from tunnel boring machines, comprising the following steps:

[0056] S1. Premix the surface-modified shield tunnel waste soil coarse aggregate and biodegradable pore-forming agent particles in a dry state for 4.5 minutes;

[0057] S2. Add the cementitious material and dry mix for 7.5 minutes to form a continuous coating layer on the surface of the aggregate;

[0058] S3. Dissolve the additive in water to form a solution, and slowly add it to the above mixture at a rate of 75 mL / min. Stir at 300 rpm for 14 minutes until the slump of the mixture reaches 100 mm.

[0059] S4. The mixture is poured into a mold and compacted using a vibrating table with a vibration frequency of 65Hz for 67 seconds. During the mixing process, the system temperature is maintained at 30℃ by a circulating water bath.

[0060] S5. Under standard curing conditions of 20±2℃ and relative humidity ≥95%, the concrete is cured to the designed age. The pore-forming agent particles remain stable for the first 48 hours to provide early strength development for the concrete. From the 3rd to the 7th day, the outer shell gradually degrades to form initial pores. From the 7th to the 28th day, the inner core fully degrades to form the final interconnected pore network.

[0061] Example 1 employs a relatively conservative, moderate parameter configuration, prioritizing stability and reliability. This scheme uses a moderate amount of pore-forming agent (8.0 parts) and a moderate amount of cementitious material (25 parts) to ensure the concrete has a good foundation of mechanical properties. The coarse aggregate is a moderate size of 14.0 mm, and surface modification is performed using a 3.5% moderate concentration silane solution at 50°C for 3 hours, resulting in a 45% increase in bond strength. The pore-forming agent is designed as a moderately crosslinked combination (17.5% core, 8.0% shell), with a relatively mild degradation process and a total degradation rate of 80%. All process parameters in this example are selected from the median range: stirring speed 400 rpm, curing temperature 25°C, and vibration frequency 65 Hz. The overall scheme is mature and stable, suitable for use as a standard formulation.

[0062] Example 2

[0063] A permeable concrete material based on shield tunneling waste soil comprises the following components in parts by weight: 88 parts of surface-modified shield tunneling waste soil coarse aggregate, 12.0 parts of biodegradable pore-forming agent particles, 20 parts of cementitious material, 22 parts of water, 0.7 parts of admixture and 1.5 parts of fine aggregate.

[0064] The surface-modified shield tunnel waste soil coarse aggregate is obtained by surface modification of shield tunnel waste soil coarse aggregate with γ-aminopropyltriethoxysilane;

[0065] The mineral composition of the coarse aggregate of the tunnel boring machine waste soil is as follows: quartz content 18.0 wt%, feldspar content 22.0 wt%, and total clay mineral content 55.0 wt%, of which montmorillonite content does not exceed 12.0 wt% of the total clay mineral content;

[0066] The biodegradable pore-forming agent particles are spherical particles with a double-layer cross-linked structure designed with corn starch as the base material. The core is modified with highly cross-linked glutaraldehyde to provide structural stability, while the outer shell is modified with low-cross-linked glutaraldehyde to achieve staged degradation. They are prepared by rotary granulation.

[0067] In this embodiment, the mass ratio of coarse aggregate from tunnel boring machine waste soil to biodegradable pore-forming agent particles is 88:12.

[0068] Furthermore, the biodegradable pore-forming agent particles adopt a double-layer cross-linked structure design, with a core cross-linking degree of 19.5% and an outer shell cross-linking degree of 6.5%. The average size of the core is 3.0 mm, and the total size after the outer shell is coated is 4.0 mm. It maintains structural stability within the first 48 hours after concrete pouring, with a degradation rate of <5%. The outer shell begins to degrade on day 37, with a degradation rate of 32%. The core is fully degraded from day 7 to day 28, with a total degradation rate of 85%. Its degradation kinetics are divided into two stages: the rate constant k1 is 0.05 d⁻¹ in the early stage (0-7 days) and the rate constant k2 is 0.16 d⁻¹ in the later stage (7-28 days).

[0069] The method for preparing coarse aggregate from tunnel boring machine waste soil in this embodiment includes the following steps performed sequentially: First, the waste soil is dehydrated and passed through a 5mm square-hole sieve to obtain a silty clay substrate with a moisture content of 18%; then, a compound curing agent prepared by mixing 42.5 grade ordinary Portland cement, Grade II quicklime, and Class F fly ash in a mass ratio of 1:0.9:1.1 is added, and the mixing water is adjusted to achieve a liquidity index of 0.3; next, the mixture is stirred at 380 rpm for 25 minutes in a twin-shaft forced mixer, and then 8mm ellipsoidal particles are prepared by a 9MPa roller granulator; subsequently, the mixture is cured for 21 days at 22℃ and 88% relative humidity, using a mist curing system instead of directly spraying carbonate buffer; finally, after sieve grading, the coarse aggregate from the tunnel boring machine waste soil is obtained.

[0070] The average size of the coarse aggregate from the shield tunneling waste soil in this embodiment is 10.5 mm.

[0071] The method for preparing the bilayer structure of the pore-forming agent particles in this embodiment includes the following steps: First, corn starch is dried to a moisture content ≤3%, mixed with water at a mass ratio of 1:2.8, and gelatinized by stirring at 77°C for 32 minutes; after the gelatinized liquid is cooled to 52°C, 0.35% of glutaraldehyde by weight of the dry starch is added to carry out the core crosslinking reaction, the pH value is controlled at 6.6, and the reaction is carried out at a constant temperature for 105 minutes; after the reaction is completed, 0.42% of sodium sulfite by weight of the dry starch is added to terminate the reaction; then the reaction product is shaped into core particles by passing it through a rotary granulator with a sieve aperture of 5 mm and a rotation speed of 30 rpm; after the core particles are dried to a moisture content ≤3%, they are immersed in a starch gelatinized liquid containing 0.12% glutaraldehyde to coat the outer shell with a coating thickness of 0.25 mm, and reacted at 52°C for 33 minutes; finally, they are dried at 57°C for 2.2 hours until the moisture content is ≤5%, and the pore-forming agent particles with the bilayer crosslinking structure are collected.

[0072] The cementitious material in this embodiment is composed of 42.5 grade ordinary Portland cement and F type fly ash in a mass ratio of 1:0.2. The hydration products contain 22.5 wt% calcium hydroxide, 9.5 wt% ettringite, 52.0 wt% hydrated calcium silicate gel, and the balance unreacted cement.

[0073] The admixture in this embodiment includes a retarder, which is selected from sodium citrate.

[0074] The preparation method of surface-modified shield tunnel waste soil coarse aggregate in this embodiment includes the following steps: First, the cured aggregate is rinsed with deionized water to remove loose particles and soluble salts from the surface, and then dried at 42°C for 1.2 hours; then, a 2.5% (w / w) γ-aminopropyltriethoxysilane ethanol solution is prepared, and the pH is adjusted to 4.2 to promote silane hydrolysis; next, the aggregate is immersed in the solution with a liquid-to-solid ratio of 3.5:1, and treated at 45°C for 2.5 hours; after treatment, it is dried at 52°C for 1.3 hours to allow silane molecules to condense on the aggregate surface to form a stable organosilicon modified layer. After this treatment, the bond strength between the aggregate and cement paste can be increased by 35% compared with the untreated aggregate.

[0075] The fine aggregate in this embodiment is natural sand with a fineness modulus of 2.4.

[0076] This embodiment describes a method for preparing permeable concrete material based on waste soil from tunnel boring machines, comprising the following steps:

[0077] S1. Premix the surface-modified shield tunnel waste soil coarse aggregate and biodegradable pore-forming agent particles in a dry state for 3.5 minutes;

[0078] S2. Add the cementitious material and dry mix for 6 minutes to form a continuous coating layer on the surface of the aggregate;

[0079] S3. Dissolve the additive in water to form a solution, and slowly add it to the above mixture at a rate of 60 mL / min. Stir at 270 rpm for 12 minutes until the slump of the mixture reaches 90 mm.

[0080] S4. Pour the mixture into a mold, and compact it using a vibrating table with a vibration frequency of 55Hz for 55 seconds. During the mixing process, maintain the system temperature at 27℃ using a circulating water bath.

[0081] S5. Under standard curing conditions of 20±2℃ and relative humidity ≥95%, the concrete is cured to the designed age. The pore-forming agent particles remain stable for the first 48 hours to provide early strength development for the concrete. On the 37th day, the outer shell gradually degrades to form initial pores. On the 728th day, the inner core fully degrades to form the final interconnected pore network.

[0082] Example 2 is specifically optimized for high permeability, employing a higher pore-forming agent dosage of 12.0 parts and a relatively lower cementitious material dosage of 20 parts to maximize porosity. Smaller coarse aggregate sizes of 10.5 mm are selected to increase specific surface area, and the pore-forming agent particles also use a smaller overall size of 4.0 mm, which facilitates a more uniform pore distribution. Surface modification is performed under milder conditions (2.5% silane concentration, 45°C treatment) to avoid excessive modification that could affect permeability. This example features a more aggressive degradation kinetic design, reducing the shell crosslinking degree to 6.5% to ensure rapid formation of permeable channels, achieving a total degradation rate of 85%. Relatively mild process parameters are selected, with a stirring speed of 270 rpm and a vibration frequency of 55 Hz, focusing on maintaining the integrity of the pore structure.

[0083] Example 3

[0084] A permeable concrete material based on shield tunneling waste soil comprises the following components in parts by weight: 93 parts of surface-modified shield tunneling waste soil coarse aggregate, 6.5 parts of biodegradable pore-forming agent particles, 32 parts of cementitious material, 15 parts of water, 1.3 parts of admixture and 2.8 parts of fine aggregate;

[0085] The surface-modified shield tunnel waste soil coarse aggregate is obtained by surface modification of shield tunnel waste soil coarse aggregate with γ-aminopropyltriethoxysilane;

[0086] The mineral composition of the coarse aggregate of the tunnel boring machine waste soil is as follows: quartz content 30.0 wt%, feldspar content 13.0 wt%, and total clay mineral content 45.0 wt%, of which montmorillonite content does not exceed 18.0 wt% of the total clay mineral content;

[0087] The biodegradable pore-forming agent particles are spherical particles with a double-layer cross-linked structure designed with corn starch as the base material. The core is modified with highly cross-linked glutaraldehyde to provide structural stability, while the outer shell is modified with low-cross-linked glutaraldehyde to achieve staged degradation. They are prepared by rotary granulation.

[0088] In this embodiment, the mass ratio of coarse aggregate from tunnel boring machine waste soil to biodegradable pore-forming agent particles is 93:6.5.

[0089] Furthermore, the biodegradable pore-forming agent particles adopt a double-layer cross-linked structure design, with a core cross-linking degree of 16.0% and an outer shell cross-linking degree of 9.5%. The average core size is 5.5 mm, and the total size after outer shell coating is 7.5 mm. It maintains structural stability within the first 48 hours after concrete pouring, with a degradation rate of <5%. The outer shell begins to degrade on day 37, with a degradation rate of 28%. The core is fully degraded on day 728, with a total degradation rate of 75%. Its degradation kinetics are divided into two stages: the rate constant k1 is 0.07 d⁻¹ on day 07 and the rate constant k2 is 0.13 d⁻¹ on day 728.

[0090] The method for preparing coarse aggregate from tunnel boring machine waste soil in this embodiment includes the following steps performed sequentially: First, the waste soil is dehydrated and passed through a 5mm square-hole sieve to obtain a silty clay substrate with a moisture content of 23%; then, a compound curing agent prepared by mixing 42.5 grade ordinary Portland cement, grade II quicklime, and type F fly ash in a mass ratio of 1:1.1:0.95 is added, and the mixing water is adjusted to achieve a liquidity index of 0.5; next, the mixture is stirred at 420 rpm for 35 minutes in a twin-shaft forced mixer, and then 16mm ellipsoidal particles are prepared by a 11MPa roller granulator; subsequently, the mixture is cured for 10 days at 28℃ and 92% relative humidity, using a mist curing system instead of directly spraying carbonate buffer solution; finally, after sieve grading, the coarse aggregate from the tunnel boring machine waste soil is obtained.

[0091] The average size of the coarse aggregate from the shield tunneling waste soil in this embodiment is 17.5 mm.

[0092] The method for preparing the bilayer structure of the pore-forming agent particles in this embodiment includes the following steps: First, corn starch is dried to a moisture content ≤3%, mixed with water at a mass ratio of 1:3.3, and gelatinized by stirring at 83°C for 38 minutes; after the gelatinized liquid is cooled to 58°C, 0.45% of glutaraldehyde by weight of the dry starch is added to carry out the core crosslinking reaction, the pH value is controlled at 7.0, and the reaction is carried out at a constant temperature for 115 minutes; after the reaction is completed, 0.48% of sodium sulfite by weight of the dry starch is added to terminate the reaction; then the reaction product is shaped into core particles by passing it through a rotary granulator with a sieve aperture of 8 mm and a rotation speed of 40 rpm; after the core particles are dried to a moisture content ≤3%, they are immersed in a starch gelatinized liquid containing 0.18% glutaraldehyde to coat the outer shell with a coating thickness of 0.45 mm, and reacted at 58°C for 42 minutes; finally, they are dried at 63°C for 2.8 hours until the moisture content is ≤5%, and the pore-forming agent particles with the bilayer crosslinking structure are collected.

[0093] The cementitious material in this embodiment is composed of 42.5 grade ordinary Portland cement and F type fly ash in a mass ratio of 1:0.4. The hydration products contain 18.0 wt% calcium hydroxide, 13.0 wt% ettringite, 44.0 wt% hydrated calcium silicate gel, and the balance unreacted cement.

[0094] The admixture in this embodiment includes a retarder, which is selected from sodium citrate.

[0095] The preparation method of surface-modified shield tunnel waste soil coarse aggregate in this embodiment includes the following steps: First, the cured aggregate is rinsed with deionized water to remove loose particles and soluble salts from the surface, and then dried at 48°C for 1.8 hours; then, a 4.5% (w / w) γ-aminopropyltriethoxysilane ethanol solution is prepared, and the pH is adjusted to 4.8 to promote silane hydrolysis; next, the aggregate is immersed in the solution with a liquid-to-solid ratio of 4.5:1, and treated at 58°C for 3.5 hours; after treatment, it is dried at 58°C for 1.8 hours to allow silane molecules to condense on the aggregate surface to form a stable organosilicon modified layer. After this treatment, the bond strength between the aggregate and cement paste can be increased by 55% compared with the untreated aggregate.

[0096] The fine aggregate in this embodiment is natural sand with a fineness modulus of 2.9.

[0097] This embodiment describes a method for preparing permeable concrete material based on waste soil from tunnel boring machines, comprising the following steps:

[0098] S1. Premix the surface-modified shield tunnel waste soil coarse aggregate and biodegradable pore-forming agent particles in a dry state for 5.5 minutes;

[0099] S2. Add the cementitious material and dry mix for 9 minutes to form a continuous coating layer on the surface of the aggregate;

[0100] S3. Dissolve the additive in water to form a solution, and slowly add it to the above mixture at a rate of 90 mL / min. Stir at 330 rpm for 16 minutes until the slump of the mixture reaches 110 mm.

[0101] S4. Pour the mixture into a mold, and compact it using a vibrating table with a vibration frequency of 75Hz for 80 seconds. During the mixing process, maintain the system temperature at 33℃ using a circulating water bath.

[0102] S5. Under standard curing conditions of 20±2℃ and relative humidity ≥95%, the concrete is cured to the designed age. The pore-forming agent particles remain stable for the first 48 hours to provide early strength development for the concrete. On the 37th day, the outer shell gradually degrades to form initial pores. On the 728th day, the inner core fully degrades to form the final interconnected pore network.

[0103] Example 3 focuses on optimizing strength performance, using 32 parts of high-cementing material combined with a lower pore-forming agent dosage of 6.5 parts to maximize mechanical properties while ensuring a certain level of permeability. Larger 17.5mm coarse aggregates were selected to provide better skeletal support. Surface modification involved treating the aggregates with a high-concentration 4.5% silane solution at 58°C for 3.5 hours, resulting in a significant 55% increase in bond strength. The pore-forming agent was designed with large particles (7.5mm total size), a moderate core crosslinking degree (16.0%), and a high outer shell crosslinking degree (9.5%) to ensure early strength development. This example utilizes relatively high process parameters: a stirring speed of 330 rpm and a vibration frequency of 75 Hz, fully leveraging the advantages of the high-cementing material dosage, making it suitable for applications with high strength requirements.

[0104] Example 4

[0105] A permeable concrete material based on shield tunneling waste soil comprises the following components in parts by weight: 86 parts of surface-modified shield tunneling waste soil coarse aggregate, 13.5 parts of biodegradable pore-forming agent particles, 28 parts of cementitious material, 24 parts of water, 1.4 parts of admixture and 1.2 parts of fine aggregate.

[0106] The surface-modified shield tunnel waste soil coarse aggregate is obtained by surface modification of shield tunnel waste soil coarse aggregate with γ-aminopropyltriethoxysilane;

[0107] The mineral composition of the coarse aggregate of the tunnel boring machine waste soil is as follows: quartz content 32.0 wt%, feldspar content 20.0 wt%, and total clay mineral content 42.0 wt%, of which montmorillonite content does not exceed 8.0 wt% of the total clay mineral content;

[0108] The biodegradable pore-forming agent particles are spherical particles with a double-layer cross-linked structure designed with corn starch as the base material. The core is modified with highly cross-linked glutaraldehyde to provide structural stability, while the outer shell is modified with low-cross-linked glutaraldehyde to achieve staged degradation. They are prepared by rotary granulation.

[0109] In this embodiment, the mass ratio of coarse aggregate from tunnel waste soil to biodegradable pore-forming agent particles is 86:13.5.

[0110] Furthermore, the biodegradable pore-forming agent particles adopt a double-layer cross-linked structure design, with a core cross-linking degree of 18.5% and an outer shell cross-linking degree of 7.5%. The average core size is 2.5 mm, and the total size after outer shell coating is 3.2 mm. It maintains structural stability within the first 48 hours after concrete pouring, with a degradation rate of <5%. The outer shell begins to degrade on day 37, with a degradation rate of 34%. The core is fully degraded on day 728, with a total degradation rate of 88%. Its degradation kinetics are divided into two stages: the rate constant k1 is 0.045 d⁻¹ on day 07 and the rate constant k2 is 0.17 d⁻¹ on day 728.

[0111] The method for preparing coarse aggregate from tunnel boring machine waste soil in this embodiment includes the following steps performed sequentially: First, the waste soil is dehydrated and passed through a 5mm square-hole sieve to obtain a silty clay substrate with a moisture content of 16%; then, a compound curing agent prepared by mixing 42.5 grade ordinary Portland cement, Grade II quicklime, and Class F fly ash at a mass ratio of 1:0.85:1.05 is added, and the mixing water is adjusted to achieve a liquidity index of 0.25; next, the mixture is stirred at 360 rpm for 22 minutes in a twin-shaft forced mixer, and then 6mm ellipsoidal particles are prepared by passing the mixture through an 8.5MPa roller granulator; subsequently, the mixture is cured for 25 days at 24℃ and 87% relative humidity, using a mist curing system instead of directly spraying carbonate buffer solution; finally, after sieve grading, the coarse aggregate from the tunnel boring machine waste soil is obtained.

[0112] The average size of the coarse aggregate from the tunnel boring machine waste soil in this embodiment is 9.5 mm.

[0113] The method for preparing the bilayer structure of the pore-forming agent particles in this embodiment includes the following steps: First, corn starch is dried to a moisture content ≤3%, mixed with water at a mass ratio of 1:2.6, and gelatinized by stirring at 76°C for 31 minutes; after the gelatinized liquid is cooled to 51°C, 0.32% glutaraldehyde by mass of the dry starch is added to carry out the core crosslinking reaction, the pH value is controlled at 6.7, and the reaction is carried out at a constant temperature for 102 minutes; after the reaction is completed, 0.41% sodium sulfite by mass of the dry starch is added to terminate the reaction; then the reaction product is shaped into core particles by passing it through a rotary granulator with a sieve aperture of 4.5 mm and a rotation speed of 28 rpm; after the core particles are dried to a moisture content ≤3%, they are immersed in a starch gelatinized liquid containing 0.11% glutaraldehyde for outer shell coating, the coating thickness is 0.22 mm, and the reaction is carried out at 51°C for 31 minutes; finally, the particles are dried at 56°C for 2.1 hours until the moisture content is ≤5%, and the pore-forming agent particles with the bilayer crosslinking structure are collected.

[0114] The cementitious material in this embodiment is composed of 42.5 grade ordinary Portland cement and F type fly ash in a mass ratio of 1:0.35. The hydration products contain 24.0 wt% calcium hydroxide, 10.5 wt% ettringite, 49.5 wt% hydrated calcium silicate gel, and the balance unreacted cement.

[0115] The admixture in this embodiment includes a retarder, which is selected from sodium citrate.

[0116] The preparation method of surface-modified shield tunnel waste soil coarse aggregate in this embodiment includes the following steps: First, the cured aggregate is rinsed with deionized water to remove loose particles and soluble salts from the surface, and then dried at 43°C for 1.3 hours; then, a 3.0% (w / w) γ-aminopropyltriethoxysilane ethanol solution is prepared, and the pH is adjusted to 4.3 to promote silane hydrolysis; next, the aggregate is immersed in the solution with a liquid-to-solid ratio of 3.8:1, and treated at 47°C for 2.8 hours; after treatment, it is dried at 53°C for 1.4 hours to allow silane molecules to condense on the aggregate surface to form a stable organosilicon modified layer. After this treatment, the bond strength between the aggregate and cement paste can be increased by 40% compared with the untreated aggregate.

[0117] In this embodiment, the fine aggregate is natural sand with a fineness modulus of 2.5.

[0118] This embodiment describes a method for preparing permeable concrete material based on waste soil from tunnel boring machines, comprising the following steps:

[0119] S1. Premix the surface-modified shield tunnel waste soil coarse aggregate and biodegradable pore-forming agent particles in a dry state for 4 minutes;

[0120] S2. Add the cementitious material and dry mix for 8 minutes to form a continuous coating layer on the surface of the aggregate;

[0121] S3. Dissolve the additive in water to form a solution, and slowly add it to the above mixture at a rate of 85 mL / min. Stir at 280 rpm for 15 minutes until the slump of the mixture reaches 95 mm.

[0122] S4. Pour the mixture into a mold, and compact it using a vibrating table with a vibration frequency of 60Hz for 70 seconds. During the mixing process, maintain the system temperature at 28℃ using a circulating water bath.

[0123] S5. Under standard curing conditions of 20±2℃ and relative humidity ≥95%, the concrete is cured to the designed age. The pore-forming agent particles remain stable for the first 48 hours to provide early strength development for the concrete. On the 37th day, the outer shell gradually degrades to form initial pores. On the 728th day, the inner core fully degrades to form the final interconnected pore network.

[0124] Example 4 employs a balanced optimization design concept, achieving an optimal balance between permeability and strength through precise adjustment of the component ratios. The pore-forming agent dosage of 13.5 parts is close to the upper limit, but combined with a moderately high proportion of 28 parts of cementitious material, a synergistic effect is achieved through optimized mineral composition (high quartz content 32.0%, low montmorillonite content 8.0%) and precise crosslinking control (core 18.5%, shell 7.5%). Smaller coarse aggregate (9.5mm size) is selected to complement the small-sized pore-forming agent particles (3.2mm), forming a multi-layered porous structure. This example exhibits the most aggressive degradation kinetics design, with a later-stage rate constant reaching 0.17d⁻¹ and a total degradation rate as high as 88%, ensuring the formation of a highly efficient interconnected pore network. The process parameters are moderately configured, emphasizing precise control, making it suitable for engineering applications with high overall performance requirements.

[0125] Comparative Example 1: It is basically the same as Example 1, except that the surface-modified shield tunnel waste soil coarse aggregate is directly replaced by shield tunnel waste soil coarse aggregate without surface modification treatment, that is, the γ-aminopropyltriethoxysilane surface modification treatment step is omitted, and the shield tunnel waste soil coarse aggregate after curing and sieve grading is used directly.

[0126] Comparative Example 2: Basically the same as Example 1, except that the biodegradable pore-forming agent particles adopt a single-layer cross-linking structure design instead of a double-layer cross-linking structure. Specifically, corn starch is dried to a moisture content of ≤3%, then mixed with water at a mass ratio of 1:3.0, and stirred at 80°C for 35 minutes for gelatinization. After the gelatinized liquid is cooled to 55°C, 0.4% of glutaraldehyde by mass of dry starch is added for uniform cross-linking reaction. The pH value is controlled at 6.8, and the reaction is kept at a constant temperature for 110 minutes. After the reaction is completed, 0.45% of sodium sulfite by mass of dry starch is added to terminate the reaction. Then, single-layer cross-linked pore-forming agent particles are prepared by rotary granulation.

[0127] Comparative Example 3: Basically the same as Example 1, except that the surface modifier is 3-aminopropyltrimethoxysilane instead of γ-aminopropyltriethoxysilane. The surface modification preparation method is to prepare a 3.5% (w / w) 3-aminopropyltrimethoxysilane ethanol solution, adjust the pH to 4.5, immerse the aggregate in the solution, set the liquid-solid ratio to 4:1, treat at 50°C for 3 hours, and dry at 55°C for 1.5 hours after treatment.

[0128] Comparative Example 4: It is basically the same as Example 1, except that the substrate of the biodegradable pore-forming agent particles uses potato starch instead of corn starch. The preparation method is to dry the potato starch to a moisture content of ≤3%, mix it with water at a mass ratio of 1:3.0, and stir it at 78°C for 33 minutes for gelatinization. The remaining steps for preparing the double-layer cross-linked structure are kept the same in terms of glutaraldehyde dosage and reaction conditions.

[0129] Comparative Example 5: It is basically the same as Example 1, except that the curing agent composition of the coarse aggregate of the shield tunnel waste soil is changed to use only 42.5 grade ordinary Portland cement, without adding Grade II quicklime and F type fly ash, and the amount of curing agent added is calculated as 12% of the dry soil mass, while the other preparation process conditions remain unchanged.

[0130] Comparative Example 6: It is basically the same as Example 1, except that the biodegradable pore-forming agent particles are formed by replacing the rotary granulation method with the traditional drop-addition granulation method. Specifically, the starch paste after the cross-linking reaction is added dropwise to the 0.5% CaCl2 solution at a rate of 2 mL / min through a syringe for ion gelation. After forming irregular spherical particles, they are washed with deionized water and dried.

[0131] Comparative Example 7: Basically the same as Example 1, except that the cementitious material composition was changed to 42.5 grade ordinary Portland cement and slag powder in a mass ratio of 1:0.3, replacing the original combination of cement and F-type fly ash. The specific surface area of ​​the slag powder was 400±20 m². 2 / kg, with an activity index of not less than 75%.

[0132] Comparative Example 8: It is basically the same as Example 1, except that the crosslinking agent for the biodegradable pore-forming agent particles is epichlorohydrin instead of glutaraldehyde. The preparation method is to add 0.6% of the dry starch mass of epichlorohydrin to the starch gelatinized liquid after cooling to 55°C to carry out the crosslinking reaction, control the pH value to 8.5, and react at a constant temperature for 90 minutes. After the reaction is completed, the pH is adjusted to neutral with dilute hydrochloric acid.

[0133] Comparative Example 9: It is basically the same as Example 1, except that the curing method of the coarse aggregate of the tunnel boring machine waste soil adopts natural drying instead of the atomized curing system. Specifically, the granulated particles are dried and cured in the outdoor natural environment with an ambient temperature of 1535℃ and a relative humidity of 4080% for 14 days, during which no artificial humidity control is carried out.

[0134] Comparative Example 10: Basically the same as Example 1, except that the cross-linking degree of the core of the biodegradable pore-forming agent particles is reduced to 8.0% and the cross-linking degree of the shell is increased to 15.0%. The preparation method is adjusted accordingly: 0.15% of glutaraldehyde by weight of dry starch is added when the core is cross-linked, and starch gelatinization liquid containing 0.3% glutaraldehyde is used when the shell is coated. The other preparation conditions remain unchanged.

[0135] Performance testing:

[0136] Permeability Performance Test: The test object is a cubic specimen of permeable concrete material based on shield tunnel waste soil, with dimensions of 150mm × 150mm × 150mm. The purpose of the test is to evaluate the permeability coefficient and permeability stability of the material, which are the core functional indicators of permeable concrete. The test principle is based on Darcy's law, calculating the permeability coefficient by measuring the water flow rate per unit area of ​​material per unit time under a certain water pressure difference. The experimental method adopts a constant head permeability test. The specimen is installed in a permeability meter, a constant head of 0.1MPa is applied, and the flow rate and seepage time under stable seepage conditions are recorded. At the same time, water temperature changes are monitored for temperature correction. The standard basis is GB / T 25993-2010 "Permeable Pavement Bricks and Permeable Pavement Panels" and CJJ / T 135-2009 "Technical Specification for Permeable Cement Concrete Pavement". Key parameters included a test temperature of 20±2℃, relative humidity of 60±5%, water head height of 100mm, a test time of no less than 10 minutes, and no less than 6 specimens per group. Data processing was performed according to the formula K=QL / (AHt), where Q is the water permeability, L is the specimen thickness, A is the permeable area, H is the water head height, and t is the permeability time. The results were taken as the logarithmic mean and the coefficient of variation was evaluated.

[0137] Compressive strength performance test: The test object is a 100mm×100mm×100mm cube standard specimen prepared from permeable concrete material based on shield tunnel waste soil, which is tested after 28 days of standard curing. The purpose of the test is to evaluate the load-bearing capacity and structural integrity of the material to ensure that it meets the strength requirements of pavement engineering. The test principle is based on the failure mechanism of the material under uniaxial compressive load, and the maximum load-bearing capacity is determined by gradually increasing the pressure until the specimen fails. The experimental method uses a compression testing machine to continuously and uniformly load the specimen at a constant loading rate of 0.5-0.8MPa / s until the specimen fails, and records the maximum load value at failure, while observing the failure mode and crack development pattern. The standard basis is GB / T 50081-2019 "Standard Test Methods for Physical and Mechanical Properties of Concrete" and ASTM C39 / C39M-2018 "Standard Test Method for Compressive Strength of Concrete Cylindrical Specimens". Key parameters included an ambient temperature of 20±2℃, relative humidity of 60±5%, specimen moisture content of saturated surface dry, loading rate of 0.6±0.1MPa / s, and a minimum of 3 to 6 specimens per group. Compressive strength was calculated using the formula fc = P / A, where P is the failure load and A is the compressed area. The results were taken as the arithmetic mean, and the standard deviation was calculated. Outliers exceeding ±15% of the mean were removed before recalculation.

[0138] Porosity and pore size distribution testing: The test object is an irregular small sample of permeable concrete material based on shield tunnel waste soil, with a size of approximately 10mm × 10mm × 10mm. The sample is taken from the center of a standard specimen to avoid boundary effects. The purpose of the test is to quantitatively analyze the pore structure characteristics of the material, including total porosity, effective porosity, pore size distribution, and pore connectivity, providing microstructural support for permeability performance. The test principle is based on the mercury infiltration method. Utilizing the non-wetting properties of mercury, mercury is infiltrated into pores of different sizes by gradually increasing the pressure. The pore size distribution is calculated based on the Washburn equation relating pressure and pore size. The experimental method uses a mercury porosimeter. First, the sample is dried at 110℃ for 24 hours to constant weight, then degassed under vacuum conditions. It is then placed in a sample cell for low-pressure mercury filling (0-0.2MPa) and high-pressure mercury filling (0.2-200MPa) tests, and the relationship curve between the cumulative mercury infiltration and pressure is recorded. The standards used are GB / T 21650.1-2008 "Determination of Pore Size Distribution and Porosity of Solid Materials by Mercury Intrusion Porosimetry and Gas Adsorption Methods - Part 1: Mercury Intrusion Porosimetry" and ASTM D4404-2018 "Standard Test Method for Determination of Pore Volume and Pore Size Distribution by Mercury Intrusion Porosimetry". Key parameters include test temperature 23±2℃, mercury surface tension 0.485 N / m, mercury-solid contact angle 130°, pressure range 0.1-200 MPa, and pressure step set logarithmically. Data processing uses the Washburn equation D=4γcosθ / P to calculate pore size, where γ is the mercury surface tension, θ is the contact angle, and P is the pressure. Total porosity is calculated as the ratio of mercury intrusion to sample volume. The results are expressed as pore size distribution curves and cumulative porosity curves.

[0139] Freeze-thaw cycle resistance test: The test object was a 100mm×100mm×400mm prism specimen made of permeable concrete material based on shield tunnel waste soil. The specimen was cured for 28 days under standard conditions and then saturated in water for 48 hours before testing. The purpose of the test was to evaluate the durability and structural stability of the material under repeated freeze-thaw cycles in cold regions, ensuring long-term performance. The test principle is based on the damage mechanism of the material structure caused by the internal stress generated by the volume expansion of water freezing in pores. Repeated freeze-thaw cycles simulate the effects of actual climatic conditions. The experimental method used a rapid freeze-thaw testing machine. The saturated specimen was frozen at -18±2℃ for 4 hours, and then thawed in water at 4±2℃ for 4 hours, constituting one cycle. 300 freeze-thaw cycles were continuously performed. Every 25 cycles, the dynamic elastic modulus, mass loss, and appearance changes of the specimen were measured. The standard basis was GB / T 50082-2009 "Standard Test Methods for Long-Term Performance and Durability of Ordinary Concrete" and ASTM C666 / C666M-2015 "Standard Test Methods for Concrete Resistance to Rapid Freeze-Thaw Cycles". Key parameters included freezing temperature -18±2℃, thawing temperature 4±2℃, freezing and thawing time 4±0.5 hours each, specimen saturation not less than 90%, and dynamic elastic modulus test frequency range 2000-5000Hz. Data processing used relative dynamic elastic modulus Pc=(fn / f0)2×100% and mass loss rate ΔW=(W0-Wn) / W0×100%, where fn and f0 are the transverse fundamental frequencies after n cycles and initially, respectively, and Wn and W0 are the masses after n cycles and initially, respectively. Freeze-thaw resistance was evaluated by the number of cycles required for the relative dynamic elastic modulus to drop to 60%.

[0140] Abrasion Resistance Test: The test object is a disc-shaped specimen with a diameter of 150 mm and a thickness of 50 mm, prepared from permeable concrete material based on tunnel boring machine waste soil. The surface of the specimen should be smooth and free of obvious defects. The purpose of the test is to evaluate the durability of the material surface under mechanical wear, simulating the wear of pavement materials under traffic loads. The test principle is based on the abrasive effect of abrasive on the material surface under certain pressure and rotation speed. The abrasion resistance is evaluated by measuring the change in mass or thickness before and after wear. The experimental method uses a modified Los Angeles abrasion tester. A load of 20±1 kg is applied to the surface of the specimen, and the specimen is rotated at a speed of 75±5 r / min. Standard quartz sand is used as the abrasive. The total number of revolutions is 1000. The change in mass of the specimen is measured every 200 revolutions, and the mass loss curve during the wear process is recorded. The standard basis is JC / T 446-2000 "Concrete Pavement Bricks" and ASTM C944 / C944M-2012 "Standard Test Method for Abrasion Resistance of Concrete or Mortar Surfaces". Key parameters included an ambient temperature of 20±5℃, relative humidity of 45-75%, applied load of 20±1kg, rotation speed of 75±5r / min, abrasive of 0.3-0.6mm standard quartz sand, wear path diameter of 120mm, and surface flatness deviation of the specimen not exceeding 0.5mm. Data processing employed the wear rate calculation formula Ma=(m0-mn) / A, where m0 and mn represent the mass before and after wear, respectively, and A represents the wear area. Results were expressed in g / cm³. 2 This means that the wear rate is calculated and the wear-time relationship curve is plotted simultaneously to evaluate the wear resistance level of the material.

[0141] The properties of the concrete mixtures from Examples 1-4 and Comparative Examples 1-10 are summarized in Table 1. The table shows that the coarse aggregate from the unmodified shield tunnel waste soil, lacking effective interfacial bonding improvement measures, resulted in reduced bond strength between the aggregate and the cementitious material. Simultaneously, the increased hydrophilicity of the aggregate surface made the interfacial transition zone more prone to microcracks, thus affecting the overall mechanical properties and durability. The pore-forming agent with a single-layer cross-linked structure lacked a gradient release mechanism during degradation, resulting in an uneven and uncontrollable pore formation process. This led to decreased connectivity and stability of the pore structure, consequently affecting the consistency of permeability and the overall strength of the material. Using different types of silane coupling agents altered the surface modification effect; in particular, differences in functional group structures affected the chemical bonding strength and interfacial stability with the matrix material, thus reducing the modification effect to some extent. Changing the starch matrix type affected the gelatinization characteristics, cross-linking reactivity, and degradation behavior of the pore-forming agent. Differences in the molecular structure of different starches led to changes in the final pore characteristics and distribution patterns, thus affecting the balance between permeability and mechanical properties. Simplified curing agent compositions lack the synergistic effect of multi-component cementitious systems, failing to fully leverage the complementary advantages of different cementitious materials, thus limiting curing effectiveness and long-term stability. Traditional granulation processes struggle to achieve precise control over particle shape and size, resulting in decreased uniformity and consistency of pore-forming agent particles, affecting the regularity of the final pore structure and the stability of performance. Changes in the cementitious material system affect the hydration reaction process and product composition; differences in the activity and reaction mechanisms of different admixtures may alter the strength development pattern and durability performance. Differences in the reaction mechanisms and crosslinking efficiencies of different crosslinking agents affect the structural stability and degradation control of the pore-forming agent, thereby influencing the timing of pore formation and the final material properties. Fluctuations in environmental factors and unstable curing effects under natural curing conditions affect the uniformity of the material and the consistency of final performance; in particular, insufficient control over humidity and temperature may lead to increased performance dispersion. Changes in the crosslinking degree ratio affect the matching of the inner and outer layer structures of the pore-forming agent and the control effect of the degradation gradient; inappropriate combinations of crosslinking degrees may lead to incoordination in the pore formation process and a decline in final performance.

[0142] from Figure 1 It can be observed that the permeable concrete prepared in Example 1 of the present invention exhibits a uniformly distributed pore structure 20 days after pouring. At this time, some pore-forming agent particles have not been completely degraded, indicating that the double-layer cross-linked structure design has achieved a controllable gradient degradation effect, providing an effective guarantee for the gradual formation and stabilization of pores. Figure 2 XRD phase analysis results show that the coarse aggregate of the shield tunnel waste soil is mainly composed of mineral phases such as quartz (Q), illite (I), montmorillonite (M) and calcite (C), among which quartz has the highest content and good crystallinity, providing a good mineralogical basis for the waste soil to be used as coarse aggregate for concrete. Figure 3Comparative analysis of compressive strength and freeze-thaw cycle resistance showed that each embodiment of the present invention was significantly superior to the comparative example in terms of mechanical properties and durability, achieving a good balance between strength and freeze-thaw resistance, and verifying the synergistic effect of surface-modified shield tunnel waste soil coarse aggregate and optimized cementitious material system. Figure 4 The comparison of the relationship between the permeability coefficient and the effective porosity reveals that the embodiments of the present invention achieve higher pore utilization efficiency while ensuring permeability performance, indicating that the combination of double-layer cross-linking pore-forming agent technology and surface modification technology effectively improves the connectivity and stability of the pore structure. Figure 5 The comprehensive comparison of wear loss rate and freeze-thaw resistance further confirms the overall advantages of the present invention in terms of durability. Each embodiment shows a lower wear rate and better freeze-thaw resistance, demonstrating the overall superiority of the technical solution. Figure 6 The comprehensive performance radar chart intuitively demonstrates the comprehensive improvement of the embodiment of the present invention in multiple dimensions such as permeability, mechanical properties, and durability compared to the comparative model, forming a more full and balanced performance distribution pattern. Figure 7 The performance optimization trend diagram shows that by adjusting and combining different technical parameters, the present invention has achieved systematic optimization and improvement of the performance of permeable concrete materials, providing reliable technical support and theoretical basis for the engineering application of high-performance permeable concrete materials based on shield tunnel waste soil.

[0143] Table 1. Performance summary of concrete from Examples 1-4 and Comparative Examples 1-10

[0144]

[0145] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and not to limit it. Although the present invention has been described in detail with reference to the above embodiments, those skilled in the art should understand that any equivalent structural transformations made under the concept of the present invention and using the contents of the specification and drawings of the present invention should be covered within the scope of protection of the claims of the present invention.

Claims

1. A permeable concrete material based on tunnel boring machine waste soil, characterized in that, The composition includes the following components in parts by weight: 85-95 parts of surface-modified coarse aggregate from tunnel excavation waste soil, 5.0-15 parts of biodegradable pore-forming agent particles, 15-35 parts of cementitious material, 10-25 parts of water, 0.5-1.5 parts of admixture, and 1.0-3.0 parts of fine aggregate. The surface-modified shield tunnel waste soil coarse aggregate is obtained by surface modification of shield tunnel waste soil coarse aggregate with γ-aminopropyltriethoxysilane; The mineral composition of the coarse aggregate from the tunnel boring machine waste soil is as follows: quartz content 15.0~35.0wt%, feldspar content 10.0~25.0wt%, and total clay mineral content 40.0~60.0wt%, of which montmorillonite content does not exceed 20.0wt% of the total clay mineral content; The biodegradable pore-forming agent particles are spherical particles with a double-layer cross-linked structure designed with corn starch as the base material. The core is modified with highly cross-linked glutaraldehyde to provide structural stability, while the outer shell is modified with low-cross-linked glutaraldehyde to achieve staged degradation. They are prepared by rotary granulation. The biodegradable pore-forming agent particles adopt a double-layer cross-linked structure design, with a core cross-linking degree of 15.0~20.0% and an outer shell cross-linking degree of 6.0~10.0%. The average core size is 2.0~6.0 mm, and the total size after outer shell coating is 2.5~8.0 mm. It maintains structural stability within the first 48 hours after concrete pouring, with a degradation rate of <5%. From day 3 to 7, the outer shell begins to degrade, reaching a degradation rate of 25~35%. From day 7 to 28, the core is fully degraded, with a total degradation rate of 70~85%. Its degradation kinetics are divided into two stages: the rate constant k1 is 0.04~0.08 days in the initial 0~7 days. -1 The rate constant k2 in the later 7-28 days is 0.12-0.18 d. -1 .

2. The permeable concrete material based on shield tunnel waste soil as described in claim 1, characterized in that, The mass ratio of the surface-modified shield tunnel waste soil coarse aggregate to the biodegradable pore-forming agent particles is (85~95):(5~15).

3. The permeable concrete material based on shield tunneling waste soil as described in claim 1, characterized in that, The method for preparing coarse aggregate from tunnel boring machine waste soil includes the following steps: First, the waste soil is dehydrated and passed through a 5mm square-hole sieve to obtain a silty clay substrate with a moisture content of 15-25%; then, a compound curing agent prepared by mixing 42.5 grade ordinary Portland cement, grade II quicklime, and type F fly ash at a mass ratio of 1:(0.8-1.2):(0.9-1.1) is added, and the mixing water is adjusted to achieve a liquidity index of 0.2-0.6; next, the mixture is stirred in a twin-shaft forced mixer at a speed of 350-450 rpm for 20-40 minutes, and then 5-20mm ellipsoidal particles are prepared by a roller granulator with an pressure of 8-12MPa; then, the mixture is cured for 7-28 days at 20-30℃ and relative humidity of 85-95%, using a mist curing system instead of directly spraying carbonate buffer solution; finally, after sieving, the coarse aggregate from tunnel boring machine waste soil is obtained.

4. The permeable concrete material based on shield tunneling waste soil as described in claim 1, characterized in that, The average size of the surface-modified shield tunnel waste soil coarse aggregate is 8.0~20.0 mm.

5. A permeable concrete material based on shield tunneling waste soil as described in claim 1, characterized in that, The method for preparing the bilayer structure of the pore-forming agent particles includes the following steps: First, corn starch is dried to a moisture content ≤3%, and mixed with water at a mass ratio of 1:(2.5~3.5). The mixture is then stirred at 75~85℃ for 30~40 minutes for gelatinization. After the gelatinized liquid cools to 50~60℃, 0.3~0.5% (by weight of the dry starch) of glutaraldehyde is added to carry out a core cross-linking reaction. The pH value is controlled at 6.5~7.0, and the reaction is carried out at a constant temperature for 100~120 minutes. After the reaction is completed, 0.4~0.5% (by weight of the dry starch) of corn starch is added. The reaction was terminated with sodium sulfite. The reaction product was then granulated into core particles using a rotary granulator with a sieve aperture of 4-9 mm and a rotation speed of 25-45 rpm. The core particles were dried to a moisture content of ≤3% and then immersed in a starch gelatinization solution containing 0.1-0.2% glutaraldehyde for outer shell coating, with a coating thickness of 0.2-0.5 mm. The reaction was carried out at 50-60℃ for 30-45 minutes. Finally, the particles were dried at 55-65℃ for 2-3 hours until the moisture content was ≤5%, and the pore-forming agent particles with a double-layer cross-linked structure were collected.

6. The permeable concrete material based on shield tunneling waste soil as described in claim 1, characterized in that, The cementitious material is composed of 42.5 grade ordinary Portland cement and F type fly ash in a mass ratio of 1:(0.15~0.45); The admixture includes a retarder, which is selected from sodium citrate; The fine aggregate is natural sand with a fineness modulus of 2.3 to 3.

0.

7. The permeable concrete material based on shield tunneling waste soil as described in claim 1, characterized in that, The method for preparing surface-modified coarse aggregate from tunnel boring machine waste soil includes the following steps: First, the cured aggregate is rinsed with deionized water to remove loose particles and soluble salts from the surface, and then dried at 40-50°C for 1-2 hours; then, a 2-5% (w / w) γ-aminopropyltriethoxysilane ethanol solution is prepared, and the pH is adjusted to 4.0-5.0 to promote silane hydrolysis; next, the aggregate is immersed in the solution with a liquid-to-solid ratio of 3:1-5:1, and treated at 40-60°C for 2-4 hours; after treatment, it is dried at 50-60°C for 2 hours to allow silane molecules to condense on the aggregate surface to form a stable organosilicon modified layer. After this treatment, the bond strength between the aggregate and cement paste can be increased by 30-60% compared to the untreated aggregate.

8. A method for preparing permeable concrete as described in any one of claims 1-7, characterized in that, Includes the following steps: S1. Premix the surface-modified shield tunnel waste soil coarse aggregate and biodegradable pore-forming agent particles in a dry state for 3-6 minutes; S2. Add the cementitious material and dry mix for 5-10 minutes to form a continuous coating layer on the surface of the aggregate; S3. Dissolve the additive in water to form a solution, and slowly add it to the above mixture at a rate of 50~100mL / min. Stir at a speed of 250~350rpm for 10~18 minutes until the slump of the mixture reaches 80~120mm. S4. Cast the mixture into a mold, and compact it using a vibrating table with a vibration frequency of 50~80Hz for 45~90 seconds. During the mixing process, maintain the system temperature at 25~35°C through a circulating water bath. S5. Under standard curing conditions of 20±2°C and relative humidity ≥95%, the concrete is cured to the designed age. The pore-forming agent particles remain stable for the first 48 hours to provide early strength development for the concrete. From the 3rd to the 7th day, the outer shell gradually degrades to form initial pores. From the 7th to the 28th day, the inner core fully degrades to form the final interconnected pore network.

Citation Information

Patent Citations

  • Permeable concrete

    CN109293318B

  • Fine-powder waste residue permeable sintered pavement brick and production method thereof

    CN107365164A

  • Method for preparing water-permeable burn-free product from shield muck

    CN111233409A